• Support PF! Buy your school textbooks, materials and every day products Here!

Mathematical Induction!

  • #1
The equation is: [i(i+1)=n(n+1)(n+2)/3] whereas i=1

so the beginning process would be 2+6+12+20.........+n(n+1)=n(n+1)(n+2)/3

after the equation is proven for n=1 [(1(1+1)=1(1+1)(1+2)/3] then we must prove for n=n+1

thats where i begin to stop understanding.
So...
2+6+12+20......+n(n+1)+n+1(n+1+1)??= n(n+1)(n+2)/3+n+1??

if my nonsense is correct then we are attempting to prove that n(n+1)(n+2)/3+n+1=(n+1)(n+2)

....help
 

Answers and Replies

  • #2
cepheid
Staff Emeritus
Science Advisor
Gold Member
5,192
35
It seems like you're trying to prove that:

[tex] \sum_{i=1}^n i(i+1) = \frac{n(n+1)(n+2)}{3} [/tex]

Every inductive proof has the same form. You start with a base case. In this case, n = 1.

Is it true that 1(2) = 1(2)(3)/3? Yes, so it works for the base case.

Then the argument is that if you can show that **IF** it works for n, **THEN** it works for n+1, then it must be true for all n by mathematical induction.

In other words, ASSUMING that it works for n, show that it works for n+1. If you can do that, then you can state that by mathematical induction, it works for all n.
 
  • #3
HallsofIvy
Science Advisor
Homework Helper
41,793
922
The equation is: [i(i+1)=n(n+1)(n+2)/3] whereas i=1
So you mean
[tex]\sum_{i= 1}^n i(i+1)= n(n+1)(n+2)/3[/tex]

so the beginning process would be 2+6+12+20.........+n(n+1)=n(n+1)(n+2)/3

after the equation is proven for n=1 [(1(1+1)=1(1+1)(1+2)/3] then we must prove for n=n+1
Well, not "n= n+1", that's meaning less. You mean to prove that if it is true for a given n, it is true for n+1.

thats where i begin to stop understanding.
So...
2+6+12+20......+n(n+1)+n+1(n+1+1)??= n(n+1)(n+2)/3+n+1??

if my nonsense is correct then we are attempting to prove that n(n+1)(n+2)/3+n+1=(n+1)(n+2)

....help
[tex]\sum_{i=1}^{n+1} i(i+1)= \sum_{i=1}^n i(i+1)+ (n+1)(n+1+1)= n(n+1)(n+2)/3+ (n+1)(n+2)[/tex]
and you want to prove that is equal to (n+1)(n+2)(n+3)/3, the basic formula n(n+1)(n+2)/3 with "n" replaced by "n+1".

I would recommend that the first thing you do is factor (n+1) and (n+2) out of n(n+1)(n+2)/3+ (n+1)(n+2).
 

Related Threads for: Mathematical Induction!

  • Last Post
Replies
3
Views
926
  • Last Post
Replies
3
Views
1K
  • Last Post
Replies
7
Views
2K
  • Last Post
Replies
4
Views
1K
  • Last Post
Replies
13
Views
2K
  • Last Post
Replies
1
Views
492
  • Last Post
Replies
3
Views
1K
  • Last Post
Replies
10
Views
2K
Top